2018
DOI: 10.15593/2224-9877/2018.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a Possibility Polishing of Stainless Steels Jet Electrolytic and Plasma Processing

Abstract: Продемонстрирована возможность струйной электролитно-плазменной полировки поверхности нержавеющих сталей. Показаны преимущества данного вида обработки по сравнению с обработкой изделий в электролитической ванне. Целью работы является выяснение условий, при которых происходит полирование поверхности нержавеющей стали в ходе ее обработки разными катодными модулями. Задачами работы являются оценка вольт-амперной характеристики, выбор электролита для полирования, выбор диапазона технологических режимов. В качестве… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A possible solution for the problem with polishing difficult geometries, small bores and cavities is the usage of an electrolyte jet [4,5,17,18,19,20,21,22]. Ablyaz et al [17] and Novoselov et al [22] demonstrated the possibility of polishing an object with a complex geometry with a free electrolyte jet. In the works of Alekseev et al [20] and Cornelsen et al [4], the polishing of the inner surfaces of pipes was shown.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…A possible solution for the problem with polishing difficult geometries, small bores and cavities is the usage of an electrolyte jet [4,5,17,18,19,20,21,22]. Ablyaz et al [17] and Novoselov et al [22] demonstrated the possibility of polishing an object with a complex geometry with a free electrolyte jet. In the works of Alekseev et al [20] and Cornelsen et al [4], the polishing of the inner surfaces of pipes was shown.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%